THE RELATIONSHIP BETWEEN SCHOOL PRINCIPALS’ TRANSFORMATIONAL LEADERSHIP AND TEACHERS’ WORK PRODUCTIVITY AT PUBLIC JUNIOR HIGH SCHOOLS IN PADANG UTARA DISTRICT - Andriani, Silvia; Nellitawati, Nellitawati; Jasrial, Jasrial; Luthfiani, Luthfiani (LPPM Univ. Ibn Khaldun Bogor, 2025)
a